The North American yoga therapy workforce survey. (April 2017) - Sullivan, Marlysa; Leach, Matthew; Snow, James; Moonaz, Steffany
Highlights: Yoga Therapy is an emerging and evolving complementary and integrative health (CIH) practice. Understanding the characteristics of yoga therapists informs educational needs for the field as well as the use of yoga therapists in healthcare. Yoga therapists were predominately female, middle aged, well-educated and worked part-time in mostly solo and urban or suburban locations. Although yoga therapists shared many commonalities with other CIH professions, important distinctions and obstacles have been identified. Abstract: Objective: To describe the personal, professional, practice, service and consumer characteristics of the North American yoga therapy workforce. Design: Cross-sectional, descriptive survey developed and informed by the contemporary workforce literature. A link to the e-survey was distributed to members of the International Association of Yoga Therapists. Results: 367 members responded (∼20% of eligible participants). Most were aged 40–69 years (88%) and female (91%). Almost half (42%) identified as a "seasoned yoga therapist" and few (9%) graduated from an accredited 800-h yoga therapy program. An average of 8 h/week was spent in clinical practice with many (41%) earning an annual income of <US$10, 000 from yoga therapy. Practice was informed by twenty different styles of yoga. Urban (39%) and suburban (38.1%) regions were the most common locations of practice. Most therapists conducted therapeutic yoga classes (91%) and 1:1 sessions (94%), with more than half delivering 1–10 therapeutic classes/month (53%) and 1–10 1:1 sessions/month (52%). Conditions seen most frequently were anxiety (77%), back/neck pain (77%) and joint pain/stiffness (67%). Conclusion: While yoga therapists shared demographic characteristics with other complementary and integrative health (CIH) providers, they tended to work less and earn less than their CIH counterparts. Yoga therapists were less likely to work in rural settings, possibly contributing to the underutilization of yoga in underserved populations. Improving access to yoga therapy services, identifying common core components across the various styles of yoga, and building a stronger evidence-base for key health indications may increase acceptance of, and demand for, yoga therapy.